Application of Electrospray Mass Spectrometry Toward Semi-Automated Kinase Inhibitor Screening - Partserniak, Ivan (My University, 2007)
Multi-site phosphorylation of protein targets by specific kinases is a common event used to propagate biological messages through signal transduction pathways in the context of the cellular environment and is a vital regulatory mechanism for many metabolic processes. Recent advances in the study of the protein glycogen synthase kinase-3 (GSK-3) have shed some light on the intricate role this enzyme plays within the framework ofmammalian cellular metabolism. Abnormal behaviour of GSK -3 profoundly impacts cellular function, and is implicated in Alzheimer's disease and the development of Type II Diabetes. A key issue in assaying the activity of GSK-3 is the ability to distinguish between singly and multiply phosphorylated substrates, as this enzyme has the ability to selectively phosphorylate a previously phosphorylated (primed) substrate. Given the serious nature of the disorders caused by the dysfunction of this kinase, high throughput screening of specific inhibitors from compound libraries is urgently needed. Unfortunately, many of the currently existing kinase screening technologies are geared towards monitoring single phosphorylation events and thus, are not be amenable to effective assaying of multiply phosphorylated substrates. In this thesis, a novel, solution-based assay method based on electrospray ionizationtandem mass spectrometry (ESI-MS/MS) is developed as a platform for inhibitor screening with full consideration being given to the specific nature of GSK-3 substrates and products. The semi-automated application of this assay is possible using an in-line autosampler, and is shown to be a potentially effective means for screening primed binding site inhibitors from compound mixtures, with subsequent deconvolution performed to isolate the effective molecule. Optimization of the MS-based assay required significant alterations in buffer conditions compared to those used in the standard GSK-3 radioassay based on y-32P ATP, owing to the inability of electrospray ionization to tolerate high buffer concentrations. Preliminary screening of mixtures was demonstrated, and expansion to screening of large compound libraries consisting of previously untested compounds and natural product extracts should be possible.
To investigate the adaptation of the GSK-3 MS/MS assay to allow mixture deconvolution, a preliminary study was performed on the utilization of sol-gel technology for entrapment of GSK-3 to develop a solid-phase affinity assay for pull-down of bioactive ligands identified in enzyme activity assays. This method requires the preservation of enzyme function within the silica matrix, which has not been previously demonstrated for GSK-3. The sol-gel entrapment of GSK-3, however, proved to be problematic. Implementation of a flow-through assay using immobilized GSK-3 was hampered by issues such as non-specific adsorption of the cationic substrate and inhibitors, owing to electrostatic interactions with the anionic silica matrix used for enzyme entrapment. Future work aimed at further developing and optimizing the sol-gel materials and processing methods are proposed.
Keywords: Electrospray; Mass Spectrometry; Semi-Automated Kinase; Inhibitor Screening